Analysis of Quality Control of PE Plastic Tarpaulin Products with the Fault Tree Analysis (FTA) Method at PT XYZ - Fajrina Rizki Izzati; Dwi Sukma Donoriyanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
Companies that are able to implement good quality control will be able to generate greater profits. PT Limmas Anugrah Plasindo is a manufacturing company that produces PE Plastic Tarpaulin. This company is faced with quality control problems where defective products drom production exceed company standards. So, from the problems that occurs, it is necessary to identify the defects and the causes of defects in PE Plastic Tarpaulin products and provide recommendations for improvements that must be made in tackling the problem of defects in PE Plastic Tarpaulin products defects. In identifying the causes of each defect problem can be done with the Fault Tree Analysis (FTA) is a technique used to identify risks that contribute to the occurrence of failure. From the research conducted, 4 types of defects were obtained, namely stretch woven, uneven color, folded laminate, and holes due to other objects. Of the four defects, there are 15 root causes that cause defects to occur. The highest defect was the stretch woven defects of 107.52 tons, the uneven color defect of 51.36 tons, the folded lamination defect is 35.51 tons, and the hole defect due to other objects is 28.61 tons. To achieve a significant reduction in the defect rate, improvements should be focused on defect types with the highest likelihood of occurrence, beginning with stretch woven, then uneven color, followed by folded laminate. By resolving the three most common defects, the company can lower the likelihood of product defects by 87.17%.